Metal phthalocyanine covalent organic framework material, preparation method thereof and application of metal phthalocyanine covalent organic framework material in electrocatalytic oxygen reduction

By mixing metal phthalocyanine with organic small molecules to prepare covalent organic frame materials and compounding them with functionalized carbon nanotubes, the problems of easy aggregation, poor conductivity and insufficient durability of FePc catalysts are solved, and efficient electrocatalytic oxygen reduction performance is achieved.

CN119708518AActive Publication Date: 2025-03-28ANHUI NORMAL UNIV

Patent Information

Application Number
CN202411840637.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing metal phthalocyanine catalysts such as FePc have problems such as prone to aggregation, poor conductivity and insufficient durability in electrocatalytic redox reactions, which limits their application performance.

Method used

Covalent organic framework materials are prepared by mixing metal phthalocyanine with organic small molecules, and the freezing-vacuum-thaw cycle is used to prepare and recombinate them with functionalized carbon nanotubes to regulate the microenvironment and electronic structure of the catalytic site, prevent the aggregation of catalytic sites, and improve carrier transportability and conductivity.

Benefits of technology

The efficient dispersion of the catalyst, the improvement of conductivity and the optimization of catalytic activity have been achieved, and the electrocatalytic oxygen reduction performance has been significantly improved, and the half-wave potential and ultimate current density have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708518A_ABST
    Figure CN119708518A_ABST
Patent Text Reader

Abstract

The invention provides a metal phthalocyanine covalent organic framework material as well as a preparation method and application thereof in electrocatalytic oxygen reduction, and compared with the prior art, the metal phthalocyanine covalent organic framework material is obtained by mixing metal phthalocyanine and small organic molecules, carrying out freezing-vacuum-unfreezing circulation and then reacting under a sealed condition. According to the invention, by selecting different construction elements, a microenvironment near a catalytic site is regulated and controlled on a molecular level, so that an electronic structure and an ionic environment of the catalytic site are regulated and controlled to adapt to target catalytic application. Meanwhile, due to a one-dimensional ordered pore channel structure constructed by the covalent organic framework, the transport property of current carriers is improved. In addition, by compounding with a functionalized carbon nanotube material, the conductivity of the material and the accessibility of catalytic sites are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a metal phthalocyanine covalent organic framework material and a preparation method thereof and an application thereof in electrocatalytic oxygen reduction. Background Art

[0002] The electrocatalytic oxygen reduction reaction (ORR) is a key step in novel energy storage and conversion systems such as fuel cells and metal-air batteries. The development of efficient and durable ORR electrocatalysts is considered a key technology for the development of various clean energy devices. Pt-based materials are the best ORR catalysts available due to their excellent catalytic activity and stability. However, their high price and limited resource reserves restrict their large-scale application and promote the vigorous development of non-precious metal ORR catalysts.

[0003] Currently, metal-nitrogen-carbon (MN 4 -C) active site materials are considered to be the most promising ORR catalysts to replace Pt. Transition metal phthalocyanines are typical MN 4 -C materials have aroused great interest among scholars, among which iron phthalocyanine (FePc) shows the highest ORR catalytic activity. However, current research on this type of material still faces some key challenges, such as the drawbacks of FePc's easy aggregation, poor conductivity and durability.

[0004] A Chinese patent with publication number CN 111193035 A published on May 10, 2024, discloses a method for preparing an oxygen reduction electrocatalyst of a strongly π-π conjugated defective graphene and iron phthalocyanine composite material. The disclosed technical solution is: using defective graphene and iron phthalocyanine as raw materials, an electrocatalyst with excellent oxygen reduction activity was successfully prepared, but it did not disclose how to solve the problem of easy aggregation of FePc. Summary of the invention

[0005] The object of the present invention is to provide a metal phthalocyanine covalent organic framework material and a preparation method thereof, wherein the metal phthalocyanine is mixed with an organic small molecule, and after a freeze-vacuum-thaw cycle, the metal phthalocyanine covalent organic framework material is reacted under a sealed condition. The present invention realizes the regulation of the microenvironment near the catalytic site at the molecular level by selecting different building blocks (organic small molecules), thereby regulating the electronic structure and ion environment of the catalytic site to adapt to the catalytic application of the target, and can effectively prevent the aggregation of the catalytic site. At the same time, the one-dimensional ordered pore structure of the covalent organic framework structure improves the transportability of carriers. In addition, by compounding with a functionalized carbon nanotube material, the conductivity of the material and the accessibility of the catalytic site are further improved.

[0006] Another object of the present invention is to provide an application of metal phthalocyanine covalent organic framework materials in electrocatalytic oxygen reduction. The present invention optimizes the electrocatalytic oxygen reduction performance by using a covalent organic framework that can regulate the microenvironment near the catalytic site and a composite strategy with carbon nanotubes.

[0007] The specific technical solutions of the present invention are as follows:

[0008] The preparation method of metal phthalocyanine covalent organic framework material is specifically as follows:

[0009] The metal phthalocyanine, organic small molecules, solvent and catalyst are mixed, subjected to a freeze-vacuum-thaw cycle, and reacted under sealed conditions to obtain a metal phthalocyanine covalent organic framework material.

[0010] Preferably, the preparation method is:

[0011] After adding metal phthalocyanine and organic small molecules into a solvent, ultrasonic treatment is performed to obtain a suspension, and then a catalyst is added. After a freeze-vacuum-thaw cycle, the suspension is reacted under sealed conditions to obtain a metal phthalocyanine covalent organic framework material.

[0012] The molar ratio of the metal phthalocyanine to the organic small molecule is 1-3:1-3; preferably 1:1, 1:2, 1:3, 2:1 or 3:1; more preferably 1:2;

[0013] The metal phthalocyanine is MPc-16X, wherein M is any one of Fe, Co, Ni or Cu, and X is any one of F and Cl;

[0014] The organic small molecule is any one of 9,10-dimethyl-2,3,6,7-tetrahydroxyanthracene THDMA, 1,2,4,5-benzene tetraol THB, 1,2,4,5-benzene tetraamine tetrahydrochloride TTH or 2,5-diamino-1,4-benzenedithiophene dihydrochloride DBD;

[0015] The concentration of the metal phthalocyanine in the solvent is 0.01 mol / L;

[0016] The catalyst is any one of ammonia water, trimethylamine and triethylamine; preferably triethylamine;

[0017] The solvent is mesitylene or dioxane;

[0018] More preferably, when the solvent is mesitylene, the catalyst is triethylamine; when the solvent is dioxane, the catalyst is ammonia water, trimethylamine or triethylamine.

[0019] Most preferably, when the solvent is dioxane, the catalyst is triethylamine.

[0020] The usage ratio of the metal phthalocyanine and the catalyst is 0.001 mmol / μL;

[0021] The freeze-vacuum-thaw cycle is to place the mixed solution in a container, freeze it in liquid nitrogen, evacuate it to a vacuum state, and then thaw it. This process is repeated three times to maintain the system in a vacuum state.

[0022] The reaction is carried out under sealed conditions, with a reaction temperature of 60°C-160°C and a reaction time of 3-7 days; preferably, the reaction is carried out at 120°C for 3 days;

[0023] Furthermore, after the reaction is completed, the product is filtered, washed, and then extracted to obtain a metal phthalocyanine covalent organic framework material;

[0024] The preparation method also adds carbon nanotube material;

[0025] The usage ratio of the metal phthalocyanine and the added carbon nanotube material is 0.001 mmol / mg;

[0026] The carbon nanotube material is any one of single-walled carbon nanotubes, multi-walled carbon nanotubes, short multi-walled carbon nanotubes, carboxyl carbon functionalized multi-walled carbon nanotubes, amino functionalized multi-walled carbon nanotubes or hydroxyl functionalized multi-walled carbon nanotubes; preferably amino functionalized multi-walled carbon nanotubes;

[0027] The metal phthalocyanine covalent organic framework material prepared by adding carbon nanotube material is a composite material of metal phthalocyanine covalent organic framework and carbon nanotube;

[0028] Preferably, the preparation method further includes adding carbon nanotube material:

[0029] After adding metal phthalocyanine, organic small molecules and carbon nanotube materials into a solvent, ultrasonic treatment is performed to obtain a suspension, and then a catalyst is added. After a freeze-vacuum-thaw cycle, the suspension is reacted under sealed conditions to obtain a metal phthalocyanine covalent organic framework material.

[0030] Furthermore, the metal phthalocyanine covalent organic framework and carbon nanotube composite material can also be:

[0031] 1) mixing metal phthalocyanine, organic small molecules, solvent and catalyst, subjecting the mixture to a freeze-vacuum-thaw cycle, and reacting the mixture under sealed conditions to obtain a metal phthalocyanine covalent organic framework material;

[0032] 2) physically blending the metal phthalocyanine covalent organic framework material and the carbon nanotube material to obtain a metal phthalocyanine covalent organic framework and carbon nanotube composite material;

[0033] The metal phthalocyanine covalent organic framework material provided by the invention is prepared by adopting the above method.

[0034] The invention also provides application of the metal phthalocyanine covalent organic framework material in electrocatalytic oxygen reduction.

[0035] The inventors found that covalent organic frameworks (COFs), as an emerging crystalline porous material, have attracted widespread attention due to their periodic framework, adjustability of the microenvironment of the catalytic site and good stability, and have become an ideal platform for developing ORR catalysts. Introducing FePc into the COF framework as a building block can not only direct the design of the microenvironment of the catalytic site, but also effectively prevent the aggregation of the catalytic site. In order to regulate the electronic structure around the active center Fe, different heteroatoms are introduced into the COF framework to increase electron donor or acceptor sites. At the same time, the hybrid orbits of certain heteroatoms (such as nitrogen and sulfur) and carbon atoms can enhance the π-conjugated system in COFs and promote the delocalization of electrons; in order to achieve the accessibility of the catalytic site, COFs with different pore structures and interlayer spacings are designed; further, in order to improve the overall conductivity of the material, a composite with functional carbon nanotubes is designed, which forms a strong π-π interaction with the layered 2D COFs, thereby improving the carrier migration efficiency and enhancing the catalytic activity.

[0036] Compared with the prior art, the present invention constructs a covalent organic framework structure, selects different building blocks (organic small molecules) to achieve molecular level regulation of the microenvironment near the catalytic site, and achieves the improvement of the catalytic performance of the material. At the same time, the framework structure can make the active center (MPc) in the catalytic reaction process better dispersed on the surface of the skeleton structure, compared with the single metal phthalocyanine polymer, the utilization rate of the active center is improved, and the overall performance of the material is greatly improved; the one-dimensional channel structure obtained after the covalent organic framework structure skeleton is constructed is conducive to proton and ion transmission, and the material conductivity and catalytic activity are improved to a certain extent; the halogen-containing building blocks and the hydroxyl-containing building blocks, with the connection mode of aromatic ether bonds, give the material extremely high stability, so that the material can maintain the original skeleton structure in subsequent development and utilization, and at the same time ensure the catalytic performance of the material; further, by compounding the covalent organic framework material with functionalized carbon nanotubes, the conductivity of the material is improved; at the same time, the porous structure of the carbon nanotubes can make the material better dispersed, greatly increase the specific surface area of ​​the material, and increase the chance of gas molecules contacting the catalytic center, so as to achieve the improvement of the catalytic performance of the material. The present invention applies metal phthalocyanine covalent organic framework material to electrocatalytic ORR reaction, and the synthesized composite material has more excellent electrocatalytic ORR performance (E 1 / 2 =0.92V vs. RHE), which is better than the ORR catalysts reported so far. At the same time, after comparative experiments and performance tests, the selected synthesis method and test conditions are currently the most convenient and effective methods. The products are easy to separate and purify, and the prepared materials are more environmentally friendly and effective, with industrial application prospects, and also provide new research ideas for the development of subsequent catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the structure of FePc-THDMA-COF;

[0038] Figure 2 Schematic diagram of the structure of FePc-THB-COF;

[0039] Figure 3 Schematic diagram of the structure of FePc-TTH-COF;

[0040] Figure 4 Schematic diagram of the structure of FePc-DBD-COF;

[0041] Figure 5 Field emission scanning electron microscopy image of FePc-THDMA-COF / CNTs;

[0042] Figure 6 Field emission scanning electron microscopy image of FePc-THB-COF / CNTs;

[0043] Figure 7 The infrared test results of THDMA, FePc-16F, FePc-THDMA-COF and FePc-THDMA-COF / CNTs are shown;

[0044] Figure 8 The infrared test results of THB, FePc-16F, FePc-THB-COF and FePc-THB-COF / CNTs;

[0045] Fig. 9 LSV curves of FePc-THDMA-COF under different rotation speed conditions;

[0046] Fig.10 LSV curves of FePc-THDMA-COF / CNTs under different rotation speed conditions;

[0047] Fig.11 LSV curves of FePc-THB-COF under different rotation speed conditions;

[0048] Fig.12 LSV curves of FePc-THB-COF / CNTs under different rotation speeds;

[0049] Fig.13 LSV curves of FePc-TTH-COF at different rotation speeds;

[0050] Fig.14 LSV curves of FePc-DBD-COF under different rotation speed conditions. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0053] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0054] Example 1

[0055] The preparation method of the metal phthalocyanine covalent organic framework material FePc-THDMA-COF is specifically as follows:

[0056] FePc-16F (0.02mmol, 17.12mg), THDMA (0.04mmol, 10.81mg) were added to a 10mL Pyrex tube, and 2mL of dioxane solvent was added. The mixture was ultrasonically treated for 10 minutes to form a uniform suspension, and then 20μL of triethylamine was added to the mixture. The Pyrex tube containing the suspension was placed in liquid nitrogen and frozen, and then thawed after being evacuated to a vacuum state. This was repeated three times to maintain the system in a vacuum state. The tube was sealed and heated in an oven at 120°C for three days. The black precipitate was collected by centrifugation and rinsed with acetone, dichloromethane and tetrahydrofuran THF in a Soxhlet extractor for one week respectively. The obtained material was recorded as FePc-THDMA-COF; the structure is as described Figure 1 shown.

[0057] like Figure 7 As shown, the material structure was analyzed by Fourier transform infrared spectrometer (Bruker Scientific instruments, INVENIO) at 1352 cm -1 , 963cm -1 Two groups of characteristic peaks can be observed, which are attributed to the symmetric and asymmetric stretching vibrations of the COC bonds, confirming the successful construction of the material skeleton;

[0058] The test was conducted using a CHI760E electrochemical workstation and a rotating disk electrode device. A three-electrode system was used in a five-port electrolytic cell, and Ag / AgCl electrodes and Pt sheets were used as reference electrodes and counter electrodes. The material obtained in Example 1 (5 mg), Ketjen black carbon powder (5 mg) and perfluoro Nafion resin solution (25 μL, 5 wt%) were added to a vial containing isopropanol (975 μL), and the catalyst ink slurry was obtained after ultrasonic treatment for 60 minutes. 10 mL of the obtained ink slurry was evenly coated on a disk electrode rde (disk inner diameter = 5.0 mm) to prepare a working electrode.

[0059] Use 0.1 M KOH as the electrolyte and first bubble O into it. 2 After 30 minutes, the electrolyte reached saturation state, and the disc speed was adjusted to 400, 625, 900, 1225, 1600 rpm for testing;

[0060] Fig. 9 The linear sweep voltammetry curve shown in the figure was obtained at a scan rate of 20 mV / s. It can be seen from the figure that the half-wave potential and limiting current density of FePc-THDMA-COF are 0.89 V and 5.78 mA / cm -2 .

[0061] The same preparation method as in Example 1 was used, except that the catalyst and solvent were changed, to investigate the crystallinity of the product. The results are shown in Table 1.

[0062] Table 1 Effect of different reaction conditions on the crystallinity of materials

[0063]

[0064] The higher the crystallinity of the product, the more favorable it is for carrier transport. Therefore, the most preferred solvent of the present invention is dioxane, and the catalyst is triethylamine, and the product has a strong crystallinity, which is favorable for carrier transport.

[0065] Example 2

[0066] The preparation method of the metal phthalocyanine covalent organic framework material FePc-THB-COF is specifically as follows:

[0067] FePc-16F (0.02mmol, 17.12mg), THB (0.04mmol, 5.68mg) were added to a 10mL Pyrex tube, and 2mL of dioxane solvent was added. The mixture was ultrasonically treated for 10 minutes to form a uniform suspension; then 20μL of triethylamine was added to the mixture. The Pyrex tube containing the suspension was frozen in liquid nitrogen, evacuated to a vacuum state, and then thawed. This was repeated three times to maintain the vacuum in the system. The tube was sealed and heated in an oven at 120°C for three days. The black precipitate was collected by centrifugation and rinsed with acetone, dichloromethane and THF in a Soxhlet extractor for one week respectively. The obtained material was recorded as FePc-THB-COF, and the structure is as described Figure 2 shown.

[0068] Figure 8 As shown, the material structure was analyzed by Fourier transform infrared spectrometer (Bruker Scientific instruments, INVENIO) at 1352 cm -1 , 963cm -1 Two sets of characteristic peaks can be observed, which are attributed to the symmetric and asymmetric stretching vibrations of the COC bonds, confirming the successful construction of the material skeleton.

[0069] The test was conducted using a CHI760E electrochemical workstation and a rotating disk electrode device. A three-electrode system was used in a five-port electrolytic cell, using an Ag / AgCl electrode and a Pt sheet as a reference electrode and a counter electrode. The material obtained in Example 2 (5 mg), Ketjen black carbon powder (5 mg) and a perfluoro Nafion resin solution (25 μL, 5 wt%) were added to a vial containing isopropanol (975 μL), and the catalyst ink slurry was obtained after ultrasonic treatment for 60 minutes. 10 mL of the obtained ink slurry was evenly coated on a disk electrode rde (disk inner diameter = 5.0 mm) to prepare a working electrode.

[0070] Use 0.1 M KOH as the electrolyte and first bubble O into it. 2 After 30 minutes, the electrolyte reached saturation state, and the disc speed was adjusted to 400, 625, 900, 1225, 1600 rpm for testing;

[0071] Fig.11 The linear sweep voltammetry curve shown in the figure was obtained at a scan rate of 20 mV / s. It can be seen from the figure that the half-wave potential and limiting current density of FePc-THB-COF are 0.88 V and 5.09 mA / cm -2 .

[0072] Example 3

[0073] The preparation method of the metal phthalocyanine covalent organic framework material FePc-TTH-COF is specifically as follows:

[0074] FePc-16F (0.02mmol, 17.12mg), TTH (0.04mmol, 11.36mg) were added to a 10mL Pyrex tube, and 2mL of dioxane solvent was added. The mixture was ultrasonically treated for 10 minutes to form a uniform suspension, and then 20μL of triethylamine was added to the mixture. The Pyrex tube containing the suspension was then placed in liquid nitrogen and frozen, and then thawed after being evacuated to a vacuum state. This was repeated three times to maintain the vacuum in the system. The tube was sealed and heated in an oven at 120°C for three days. The black precipitate was collected by centrifugation and rinsed with acetone, dichloromethane and THF in a Soxhlet extractor for one week respectively. The obtained material was recorded as FePc-TTH-COF; the structure is as described Figure 3 shown.

[0075] The test was conducted using a CHI760E electrochemical workstation and a rotating disk electrode device. A three-electrode system was used in a five-port electrolytic cell, and Ag / AgCl electrodes and Pt sheets were used as reference electrodes and counter electrodes. The material obtained in Example 3 (5 mg), Ketjen black carbon powder (5 mg) and perfluoro Nafion resin solution (25 μL, 5 wt%) were added to a vial containing isopropanol (975 μL), and the catalyst ink slurry was obtained after ultrasonic treatment for 60 minutes. 10 mL of the obtained ink slurry was evenly coated on a disk electrode rde (disk inner diameter = 5.0 mm) to prepare a working electrode.

[0076] Use 0.1 M KOH as the electrolyte and first bubble O into it. 2 After 30 minutes, the electrolyte reached saturation state, and the disc speed was adjusted to 400, 625, 900, 1225, 1600 rpm for testing;

[0077] Fig.13 The linear sweep voltammetry curve shown in the figure was obtained at a scan rate of 20 mV / s. It can be seen from the figure that the half-wave potential and limiting current density of FePc-TTH-COF are 0.78 V and 5.34 mA / cm -2 .

[0078] Example 4

[0079] The preparation method of the metal phthalocyanine covalent organic framework material FePc-DBD-COF is specifically as follows:

[0080] FePc-16F (0.02mmol, 17.12mg), DBD (0.04mmol, 9.80mg) were added to a 10mL Pyrex tube, and 2mL of dioxane solvent was added, and the mixture was ultrasonically treated for 10 minutes to form a uniform suspension. Then 20μL of triethylamine was added to the mixture; the Pyrex tube containing the suspension was placed in liquid nitrogen and frozen, and then thawed after being evacuated to a vacuum state. This was repeated three times to maintain the vacuum in the system. The tube was sealed and heated in an oven at 120°C for three days. The black precipitate was collected by centrifugation and rinsed with acetone, dichloromethane and THF in a Soxhlet extractor for one week respectively. The obtained material was recorded as FePc-DBD-COF; the structure is as described Figure 4 shown.

[0081] The test was conducted using a CHI760E electrochemical workstation and a rotating disk electrode device. A three-electrode system was used in a five-port electrolytic cell, and Ag / AgCl electrodes and Pt sheets were used as reference electrodes and counter electrodes. The material obtained in Example 4 (5 mg), Ketjen black carbon powder (5 mg) and perfluoro Nafion resin solution (25 μL, 5 wt%) were added to a vial containing isopropanol (975 μL), and the catalyst ink slurry was obtained after ultrasonic treatment for 60 minutes. 10 mL of the obtained ink slurry was evenly coated on a disk electrode rde (disk inner diameter = 5.0 mm) to prepare a working electrode.

[0082] Use 0.1 M KOH as the electrolyte and first bubble O into it. 2 After 30 minutes, the electrolyte reached saturation state, and the disc speed was adjusted to 400, 625, 900, 1225, 1600 rpm for testing;

[0083] Fig.14 The linear sweep voltammetry curve shown in the figure was obtained at a scan rate of 20 mV / s. It can be seen from the figure that the half-wave potential and limiting current density of FePc-DBD-COF are 0.82 V and 4.78 mA / cm -2 .

[0084] Example 5

[0085] The preparation method of the metal phthalocyanine covalent organic framework and carbon nanotube composite material FePc-THDMA-COF / CNTs is specifically as follows:

[0086] FePc-16F (0.02mmol, 17.12mg), THDMA (0.04mmol, 10.81mg) and 20mg amino-functionalized carbon nanotubes (MWCNTs) were added to a 10mL Pyrex tube, and 2mL of dioxane solvent was added. The mixture was ultrasonically treated for 10 minutes to form a uniform suspension, and then 20μL of triethylamine was added to the mixture. The Pyrex tube containing the suspension was frozen in liquid nitrogen, evacuated to a vacuum state, and then thawed. This was repeated three times to maintain the vacuum system. The tube was sealed and heated in an oven at 120°C for three days. The black precipitate was collected by centrifugation and rinsed with acetone, dichloromethane and THF in a Soxhlet extractor for one week. The resulting material was recorded as FePc-THDMA-COF / CNTs.

[0087] Figure 5 It can be seen from the field emission scanning electron microscopy image shown that FePc-THDMA-COF and amino-functionalized multi-walled carbon nanotubes are fully and evenly mixed, and the entire structure presents a loose and porous morphology, which is conducive to the exposure of active sites and gas diffusion transport;

[0088] Figure 7 As shown, the material structure was analyzed by Fourier transform infrared spectrometer (Bruker Scientific instruments, INVENIO) at 1352 cm -1 , 963cm -1 Two groups of characteristic peaks can be observed, which are attributed to the symmetric and asymmetric stretching vibrations of the COC bond, confirming the successful construction of the material skeleton and that the introduction of amino-functionalized carbon nanotubes did not destroy the framework structure of the material.

[0089] The test was conducted using a CHI760E electrochemical workstation and a rotating disk electrode device. A three-electrode system was used in a five-port electrolytic cell, and Ag / AgCl electrodes and Pt sheets were used as reference electrodes and counter electrodes. The material obtained in Example 5 (5 mg), Ketjen black carbon powder (5 mg) and perfluoro Nafion resin solution (25 μL, 5 wt%) were added to a vial containing isopropanol (975 μL), and the catalyst ink slurry was obtained after ultrasonic treatment for 60 minutes. 10 mL of the obtained ink slurry was evenly coated on a disk electrode rde (disk inner diameter = 5.0 mm) to prepare a working electrode.

[0090] Use 0.1 M KOH as the electrolyte and first bubble O into it. 2 After 30 minutes, the electrolyte reached saturation state, and the disc speed was adjusted to 400, 625, 900, 1225, 1600 rpm for testing;

[0091] Fig.10The linear sweep voltammetry curve shown in the figure was obtained at a scan rate of 20 mV / s. It can be seen from the figure that the half-wave potential and limiting current density of FePc-THDMA-COF / CNTs are 0.92 V and 6.46 mA / cm -2 .

[0092] Example 6

[0093] The preparation method of the metal phthalocyanine covalent organic framework and carbon nanotube composite material FePc-THB-COF / CNTs is specifically as follows:

[0094] FePc-16F (0.02mmol, 17.12mg), THB (0.04mmol, 5.68mg) and 20mg amino-functionalized carbon nanotubes (MWCNTs) were added to a 10mL Pyrex tube, 2mL of dioxane solvent was added, and the mixture was ultrasonically treated for 10 minutes to form a uniform suspension. Then 20μL of triethylamine was added to the mixture. The Pyrex tube containing the suspension was frozen in liquid nitrogen, evacuated to a vacuum state and then thawed. This was repeated three times to maintain the vacuum system. The tube was sealed and heated in an oven at 120°C for three days. The black precipitate was collected by centrifugation and rinsed with acetone, dichloromethane and THF in a Soxhlet extractor for one week. The resulting material was recorded as FePc-THB-COF / CNTs.

[0095] Figure 6 It can be seen from the field emission scanning electron microscopy image shown that FePc-THB-COF and amino-functionalized multi-walled carbon nanotubes are fully and evenly mixed, and the entire structure presents a loose and porous morphology, which is conducive to the exposure of active sites and gas diffusion transport.

[0096] Figure 8 As shown, the material structure was analyzed by Fourier transform infrared spectrometer (Bruker Scientific instruments, INVENIO) at 1352 cm -1 , 963cm -1 Two groups of characteristic peaks can be observed, which are attributed to the symmetric and asymmetric stretching vibrations of the COC bond, confirming the successful construction of the material skeleton and that the introduction of amino-functionalized carbon nanotubes did not destroy the framework structure of the material;

[0097] The test was conducted using a CHI760E electrochemical workstation and a rotating disk electrode device. A three-electrode system was used in a five-port electrolytic cell, using an Ag / AgCl electrode and a Pt sheet as a reference electrode and a counter electrode. The material obtained in Example 6 (5 mg), Ketjen black carbon powder (5 mg) and a perfluoro Nafion resin solution (25 μL, 5 wt%) were added to a vial containing isopropanol (975 μL), and the catalyst ink slurry was obtained after ultrasonic treatment for 60 minutes. 10 mL of the obtained ink slurry was evenly coated on a disk electrode rde (disk inner diameter = 5.0 mm) to prepare a working electrode.

[0098] Use 0.1 M KOH as the electrolyte and first bubble O into it. 2 After 30 minutes, the electrolyte reached saturation state, and the disc speed was adjusted to 400, 625, 900, 1225, 1600 rpm for testing;

[0099] Fig.12 The linear sweep voltammetry curve shown in the figure was obtained at a scan rate of 20 mV / s. It can be seen from the figure that the half-wave potential and limiting current density of FePc-THB-COF / CNTs are 0.91 V and 6.02 mA / cm -2 .

[0100] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a metal phthalocyanine covalent organic framework material, characterized in that: The preparation method is specifically: The metal phthalocyanine, organic small molecules, solvent and catalyst are mixed, subjected to a freeze-vacuum-thaw cycle, and reacted under sealed conditions to obtain a metal phthalocyanine covalent organic framework material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the metal phthalocyanine to the organic small molecule is 1-3:1-3.

3. The preparation method according to claim 1 or 2, characterized in that: The metal phthalocyanine is MPc-16X, wherein M is any one of Fe, Co, Ni or Cu; and X is any one of F and Cl.

4. The preparation method according to claim 1 or 2, characterized in that: The organic small molecule is any one of 9,10-dimethyl-2,3,6,7-tetrahydroxyanthracene, 1,2,4,5-benzenetetrol, 1,2,4,5-benzenetetraamine tetrahydrochloride or 2,5-diamino-1,4-benzenedithiophene dihydrochloride.

5. The preparation method according to claim 1, characterized in that: The solvent is mesitylene or dioxane; the catalyst is any one of ammonia water, trimethylamine and triethylamine.

6. The preparation method according to claim 1, characterized in that: The reaction is carried out under the sealed conditions, the reaction temperature is 60° C.-160° C., and the reaction time is 3-7 days.

7. The preparation method according to claim 1, characterized in that: The preparation method further adds carbon nanotube material, and the usage ratio of the metal phthalocyanine to the carbon nanotube material is 0.001 mmol / mg.

8. The preparation method according to claim 7, characterized in that: The preparation method of adding carbon nanotube material is as follows: After adding metal phthalocyanine, organic small molecules and carbon nanotube materials into a solvent, ultrasonic treatment is performed to obtain a suspension, and then a catalyst is added. After a freeze-vacuum-thaw cycle, the suspension is reacted under sealed conditions to obtain a metal phthalocyanine covalent organic framework material.

9. A metal phthalocyanine covalent organic framework material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the metal phthalocyanine covalent organic framework material according to claim 9 in electrocatalytic oxygen reduction.

Citation Information

Patent Citations

  • Preparation method of strong [pi]-[pi] conjugate defective graphene and iron phthalocyanine composite material about oxygen reduction electrocatalyst

    CN111193035A

  • Carbon nanotube-loaded metal phthalocyanine-based imide polymer catalyst as well as preparation method and application thereof

    CN117160536A

Cited By

  • Catalyst for wastewater COD (Chemical Oxygen Demand) in-situ degradation and preparation method thereof

    CN121588908A